Spanglish: linguistic aberration or linguistic hybridization? A linguistic, cultural, and literary approach - Bernal, Reygar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is a review of the linguistic, social, cultural and literary phenomenon known as Spanglish, starting from the different hybrid dialects spoken by the Latino diaspora in the United States and following their evolution towards becoming a language .
Keywords: Spanglish; languages; Latino/a; identity; culture; literature